2012
DOI: 10.11646/zootaxa.3586.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Molecular systematics of western North American cyprinids (Cypriniformes: Cyprinidae)

Abstract: The phylogenetic or evolutionary relationships of species of Cypriniformes, as well as their classification, is in a era of flux. For the first time ever, the Order, and constituent Families are being examined for relationships within a phylogenetic context. Relevant findings as to sister-group relationships are largely being inferred from analyses of both mitochondrial and nuclear DNA sequences. Like the vast majority of Cypriniformes, due to an overall lack of any phylogenetic investigation of these fishes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 63 publications
4
29
0
Order By: Relevance
“…Our phylogenetic hypothesis is largely congruent with other recent but less well-sampled phylogenies (Schönhuth et al, 2012(Schönhuth et al, , 2014Hollingsworth et al, 2013). We recovered a strongly supported sister relationship between the Western and CC-P clades, a result which Schönhuth et al (2012) found only with mitochondrial data; this may be due to the strong mitochondrial signal in our dataset or the relatively large amount of missing nuclear data. We also recovered numerous non-monophyletic genera, most of which have been noted by previous authors; the Western clade is particularly in need of revision (e.g.…”
Section: Phylogenysupporting
confidence: 89%
See 4 more Smart Citations
“…Our phylogenetic hypothesis is largely congruent with other recent but less well-sampled phylogenies (Schönhuth et al, 2012(Schönhuth et al, , 2014Hollingsworth et al, 2013). We recovered a strongly supported sister relationship between the Western and CC-P clades, a result which Schönhuth et al (2012) found only with mitochondrial data; this may be due to the strong mitochondrial signal in our dataset or the relatively large amount of missing nuclear data. We also recovered numerous non-monophyletic genera, most of which have been noted by previous authors; the Western clade is particularly in need of revision (e.g.…”
Section: Phylogenysupporting
confidence: 89%
“…We also recovered numerous non-monophyletic genera, most of which have been noted by previous authors; the Western clade is particularly in need of revision (e.g. Schönhuth et al, 2012Schönhuth et al, , 2014, while the OPM genus Notropis has long been used as a bin for species of questionable affinity. Most notably, our phylogeny did not recover the distinctive pikeminnows (genus Ptychocheilus) as monophyletic, in agreement with other studies (Simons et al, 2003;Mayden, 2010a, 2010b;Houston et al, 2010;Schönhuth et al, 2012Schönhuth et al, , 2014.…”
Section: Phylogenysupporting
confidence: 56%
See 3 more Smart Citations